2003
DOI: 10.1002/humu.9124
|View full text |Cite
|
Sign up to set email alerts
|

Mutation analysis of the entire keratin 5 and 14 genes in patients with epidermolysis bullosa simplex and identification of novel mutations

Abstract: Epidermolysis bullosa simplex is a group of blistering skin disorders caused by defects in one of the keratin genes, KRT5 and KRT14. Previously reported KRT5 and KRT14 mutations are clustered in several hotspots, namely the rod ends of the 1A and 2B domains and in the non-helical linker region L12. Therefore, genomic KRT5 and KRT14 mutation analysis was initially limited to these hotspots. In this study we describe the screening of nine EBS patients for mutations in the hotspots. In two patients, with the Koeb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
30
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(37 citation statements)
references
References 13 publications
6
30
0
Order By: Relevance
“…Overall, a single amino acid substitution was the predominant mutational event, which is consistent with previous reports [23]. Previous studies have shown that the frequencies of K5 and K14 mutations in EBS are approximately similar [16]. In this study, nine and six mutations were on K5 and K14, respectively, making the frequency of K5 mutations slightly higher than K14 mutations (60% vs 40%, respectively), although the significance of this difference was not determined.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Overall, a single amino acid substitution was the predominant mutational event, which is consistent with previous reports [23]. Previous studies have shown that the frequencies of K5 and K14 mutations in EBS are approximately similar [16]. In this study, nine and six mutations were on K5 and K14, respectively, making the frequency of K5 mutations slightly higher than K14 mutations (60% vs 40%, respectively), although the significance of this difference was not determined.…”
Section: Discussionsupporting
confidence: 92%
“…Total DNA was used as a template for amplification of the genomic sequences of KRT5 and KRT14. KRT5 segments including nine exons and all exon-intron borders and KRT14 segments including eight exons and all exon-intron borders were amplified as previously described [16,17]. Sequence analyses were performed using Big Dye terminator technology (ABI 3100 PerkinElmer, Warrington, UK).…”
Section: Mutation Analysismentioning
confidence: 99%
“…Amino acid substitutions are more common at codon 475 in patients with EBS-DM and both p.E475G and p.E475K substitutions have been reported. [20][21][22] Our analysis of cultured EBS-derived keratinocytes demonstrated some common features as well as divergence related to the phenotypic variation seen in the patients. We observed that KIF organization appeared surprisingly normal in cultures of keratinocytes isolated from these patients with EBS.…”
Section: Discussionmentioning
confidence: 93%
“…In particular, the helix initiation peptide in region 1A and the helix termination peptide in the 2B domain are important for heterodimerization of compatible type 1 and type 2 keratins (18,19). The phenotypes of the three major subtypes of EBS, EBS Dowling-Meara (EBS-DM), localized EBS (EBS-loc) and generalized other EBS are the consequence of mutations at different residues in K5 or K14 genes; mutations in the critical 1A and 2B regions lead to the most severe form, EBS-DM (20).…”
Section: Introductionmentioning
confidence: 99%